Concurrent associations of dimensions of anger with posttraumatic stress, depression, and functional impairment following non-fatal traffic accidents. Issue 1 (31st December 2022) - Boelen, Paul A.; Eisma, Maarten C.; de Keijser, Jos; Lenferink, Lonneke I.M.
ABSTRACT: Background: Anger is associated with dysfunction following potentially traumatic events. It is still unclear to what extent different types of anger are differentially related to poor outcomes. To advance knowledge in this area, the Posttraumatic Anger Questionnaire (PAQ) was designed, measuring anger directed at (i) the justice system, (ii) other people, (iii) the self, (iv) people held accountable for the potential traumatic event, and (v) a desire for revenge to those held responsible. Preliminary evidence shows that these types of anger are distinguishable and differentially associated with posttraumatic stress (PTS). No studies have yet examined whether such findings can be generalized to victims of non-fatal traffic accidents, one of the most common potentially traumatic events. Objective: This study's aims were (i) to establish if the five-factor structure of the PAQ found in prior studies could be replicated, (ii) to explore whether the intensity of emerging types of anger differed, and (iii) to explore the associations of anger-types with levels of PTS, depression, and functional impairment. Method: Two-hundred and fifty adults who experienced a traffic accident completed the PAQ and instruments measuring PTS, depression, and functional impairment. They also answered questions about their socio-demographic characteristics and features of the accident. Results: Confirmatory factor analysis confirmed that the PAQ measures five types of anger. Levels of anger at people held accountable were the highest. Structural equation modelling showed that both anger at others and anger at the self, but not the other three anger types, were associated with PTS, depression, and functional impairment, when controlling for the shared variance between the anger types, socio-demographic variables, and features of the accident. Conclusions: Findings illustrate the potential importance of considering different types of anger when assessing and treating PTS following traffic accidents. HIGHLIGHTS: Based on data from people confronted with a traffic accident, we found the Posttraumatic Anger Questionnaire (PAQ) to represent distinguishable dimensions of anger. Anger dimensions were: anger directed at (i) the justice system, (ii) other people, (iii) the self, (iv) people held accountable for the event, and (v) a desire for revenge to those held responsible. Scores on items measuring anger at people held accountable for the event were significantly higher than scores on items measuring other anger types. Anger at the self and other people were most strongly associated with posttraumatic stress, depression, and functional impairment.